Sustainability in Science Education: A Bibliometric Analysis during 2000–2022 - Sintia Mardita (Journal of Education for Sustainable Development Studies, 2024)
Sustainable has a better concept of human life amid natural limitations by always maintaining a balance of life in the social, economic, and environmental fields. One of the efforts that can be made in realizing the SDGs is through education. The concept of science and science education is considered a determining factor for achieving the SDGs. Several studies have explored the relationship between science learning in sustainability and its impact on the environment and learning outcomes. However, bibliometric studies that study in this field are still very rare, previous bibliometric studies have analyzed a lot about sustainability in the field of education both at the primary, secondary, and tertiary levels. The purpose of this study is to provide a bibliometric analysis of sustainability in science studies by analyzing documents published by Scopus. A sample of 797 documents through 2022 was analyzed. The data is processed and the results are graphically illustrated using VOSviewer software. The study analyzes the emergence of publications by year in the period 2000-2022, keyword trends, most cited references, most prolific sources, institutions, countries, and authors. In addition, the co-authorship status for the author, the country, and the distribution of author keywords are also analyzed and depicted in the form of a network visualization map in the form of lines and nodes. This research provides insights and future research opportunities on sustainability in science education.